CAPOEIRA IN THE PROCESS OF SOCIAL INCLUSION (Fiep Bulletin - online, 2014)
Capoeira can favour the critically contextualized acquisition of cultural and educational values, promoting social inclusion through the movement of art and music. Therefore, the current study suggests that capoeira, as a popular Brazilian cultural manifestation is propagated by universities through university extension projects. The objective of one of these initiatives, which was the social inclusion of children through capoeira, attended to roughly 200 children, youngsters and adults from a poor neighbourhood of Rio Branco (AC) in two and half years. Practical classes, theoretical classes, workshops and seminars were periodically carried out within these project actions. The most expressive result was from children and youngsters who quit using legal and illegal drugs. Thus, capoeira proved to be a non formal possibility of education, promoting social inclusion.
Keywords: Capoeira; Social Inclusion; Culture